PEMELIHARAAN.RUNWAY,.TAXIWAY.DAN.APRON.BANDAR.UDARA. INTERNASIONAL.AHMAD.YANI.SEMARANG. - , ARIO CAHYA GEMILANG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Ahmad Yani International Airport in Semarang became one of the airport under PT. Angkasa Pura. Ahmad Yani Airport turned into an international airport in 2004 after opening Garuda Indonesia-Singapore route Semarang. Ahmad Yani Airport in Semarang turned into Ahmad Yani International Airport in Semarang. After several years of Ahmad Yani airport has improved a lot in addition to the level of demand of increasing flight services. This should be addressed by PT. Angkasa Pura I (Persero) as a flight service manager Ahmad Yani Airport is by improving the airport facilities and maintenance. In the airport maintenance broadly divided into 2 airside facilities and landside facilities. A very important role is airside facilities including runway, taxiways and apron. Third airport facilities are very supportive, especially in the air or directly related dengsn aircraft. Therefore need special care and attention to three such facilities in order to avoid damage or reduced function of the facility. With care, foundation inspection, rubber deposite, repainting markings and controls on a regular basis in accordance with the procedure that is able to overcome the problems that can interfere with flight. A. These Yani has a runway dimension of 2,680 x 45 m2, taxiway dimensions 275 x 23 m2, 29.032 m2 apron dimension. This time to note is the apron for apron condition that used to only be used as an air base military aircraft that have a lighter weight as compared Fokker 28 commercial aircraft currently using the airport apron such as the Boeing 737 series 200, 400, 800 NG, 900 ER. Apron experienced pelendutan in beberapara point that local reduction of pavement surface ellipse with a maximum length of 5 m with a moderate degree of damage that is 1 cm <d <2 cm in accordance with the Director General of Civil Aviation Regulation No.. SKEP/78/VI/2005 dated June 20, 2005 then it should be repaired with a flexible apron pavement or paved over.